A simple mixer/jet cell for raman spectroscopic studies - Oertling, Anthony; Babcock, Gerald T.; Varotsis, Constantinos (My University, 1990)
The design of the mixer is presented. The exit port of the mixer is constructed so as to allow the flowing sample solution to form a continuous stream in air in the scattering volume, which eliminates quartz scattering. The mixer with the upper micropipet and the lower micropipet are each mounted on X-Y-Z translators, which allows us to optimize the stability of the jet. Generally, we find that a gap of approximately 2 mm is appropriate. The iris diaphragm is also mounted on an X-Y-Z positioner and serves as the laser beam waist controller. The translation stage on which the cell is mounted allows X, Y, and Z movements relative to the entrance slit of the spectrometer
Keywords: Raman spectroscopy; Biomolecules; Cytochrome oxidase